Advanced hydrogel mesh platform with neural stem cells and human umbilical vein endothelial cells for enhanced axonal regeneration - Jong-Tae Kim; Sung Woo Han; Dong Hyuk Youn; Harry Jung; Eun-Ho Lee; Sung-Min Kang; Yong-Jun Cho; Jin Pyeong Jeon (APL Bioengineering)
One of the major obstacles to neural recovery following intracerebral hemorrhage (ICH) is the cavity-like lesion that occurs at the site of the hemorrhage, which impedes axonal regeneration. Here, we aim to address this challenge by investigating the migratory mechanisms of neural stem cells (NSCs) within the cavity in vitro using a hydrogel and endothelial cells. Mouse NSCs (mNSCs) isolated from the subventricular and subgranular zones using the 3D hydrogel culture were evaluated for their neurogenic, extracellular matrix (ECM), and adhesion-related mRNA expression compared to microglia (BV2) and secretory factors of human umbilical vein endothelial cells (HUVECs) in vitro and in vivo conditions. A hydrogel mesh combining mNSCs and HUVECs was developed for its therapeutic potential. mNSCs exhibit high stemness, neurogenesis, and ECM remodeling capabilities. mNSCs demonstrated close interaction with HUVECs and the surrounding vascular structures in in vitro and in vivo studies. Furthermore, mNSCs could degrade high concentrations of fibrin to facilitate migration and adhesion. mNSCs and HUVECs formed mesh networks through cell–cell contacts and maintained the structure through Matrigel support, potentially ensuring sufficient survival and regeneration capabilities. Our proposed hydrogel mesh platform with mNSCs and HUVECs demonstrated successful maintenance of cell survival and provision of structural support for the delivered cells by promoting ECM remodeling and neurogenesis, which may aid in axonal regeneration in the cavity lesions following ICH.